2007
DOI: 10.1371/journal.pbio.0050064
|View full text |Cite
|
Sign up to set email alerts
|

Als3 Is a Candida albicans Invasin That Binds to Cadherins and Induces Endocytosis by Host Cells

Abstract: Candida albicans is the most common cause of hematogenously disseminated and oropharyngeal candidiasis. Both of these diseases are characterized by fungal invasion of host cells. Previously, we have found that C. albicans hyphae invade endothelial cells and oral epithelial cells in vitro by inducing their own endocytosis. Therefore, we set out to identify the fungal surface protein and host cell receptors that mediate this process. We found that the C. albicans Als3 is required for the organism to be endocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
617
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(654 citation statements)
references
References 67 publications
23
617
1
3
Order By: Relevance
“…Induced endocytosis is a host-driven process triggered predominantly by interaction between the C. albicans invasin, Als3, and host E-cadherin. This process results in clathrindependent uptake, similar to the internalin-E-cadherin dependent internalization of Listeria monocytogenes [36,41,42]. Under standard laboratory growth conditions, Als3 is expressed on hyphal, but not yeast cell surfaces [43].…”
Section: Hyphal Formation and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced endocytosis is a host-driven process triggered predominantly by interaction between the C. albicans invasin, Als3, and host E-cadherin. This process results in clathrindependent uptake, similar to the internalin-E-cadherin dependent internalization of Listeria monocytogenes [36,41,42]. Under standard laboratory growth conditions, Als3 is expressed on hyphal, but not yeast cell surfaces [43].…”
Section: Hyphal Formation and Invasionmentioning
confidence: 99%
“…Under standard laboratory growth conditions, Als3 is expressed on hyphal, but not yeast cell surfaces [43]. Consequently, only hyphal cells were observed to be endocytosed by epithelial and endothelial cells [36,41].…”
Section: Hyphal Formation and Invasionmentioning
confidence: 99%
“…Als3 and Ssa1 on the surface of C. albicans hyphae bind to Ncadherin and other receptors on the surface of endothelial cell, which mediates the endocytosis. [98][99][100] In contrast to the ALS proteins and endocytosis, the interaction between C. albicans PAMPs and PRRs on endothelial cells was rarely investigated. A study revealed that C. albicans triggers proinflammatory gene expression in primary human endothelial cells through TLR3 signaling, NF-kB, and p38 MAPK pathways in response to C. albicans invasion.…”
Section: Prrs Of Endothelial Cellsmentioning
confidence: 99%
“…As an example, Candida albicans may cross the intestinal barrier in an Als3-Ecad-dependent manner, leading to a systemic infection (Phan et al, 2007), but it has not been described to breach the placental barrier. This indicates that targeting of Ecad alone is not sufficient to promote placental invasion, and that C. albicans is likely missing an effector inducing PI3-K signaling at the placental barrier, as does Lm.…”
Section: Discussionmentioning
confidence: 99%